The Effectiveness of Mind Mapping in Improving Students Descriptive Writing Ability at Cokroaminoto University of Palopo - Juwita Crestiani (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
The objectives of this research were to find out whether or not mind mapping improves the students’ descriptive writing ability covering content, organization, vocabulary, language use and mechanics components; which aspects is dominantly improved by the effectiveness of mind mapping. This research applied quasi experimental method. This research consisted of assigned two groups namely experimental group and control group. Each group consisted of 30 students. The sample was chosen by purposive random sampling technique. The instrument of this research was writing test. In collecting data, this research used some procedures namely pre test, treatment, post test. In the experimental group, the students were given material through mind mapping for five times while in control group, the students were also given treatment through conventional way (lecturing method) for five times. The researcher used writing test both in experimental and control group. The data of students’ writing ability were analyzed by using inferential statistics through SPSS 17.0 version. The effectiveness of mind mapping improved the students’ writing ability in descriptive text. This is proved by the mean score of experimental group in posttest was 81.61 (good) classification. While the mean score of control group in posttest was 49.86 (poor) classifications. It was also proved by the different improvement of writing components (content, organization, vocabulary, language use, and mechanics) of both groups in the posttest which was taken from both valuators. Those improvements showed that effectiveness of mind mapping improved the students’ writing ability in the experimental group. It is more effective to improve the students’ writing ability. It indicated that the alternative hypothesis (H1) was significantly approved. Component in writing dominantly improved is content. The data result proves such conclusion which is based on the data from researcher and lecturer in the table 4.51 that showed that the mean score of content was 84.44 and it was higher than the other components.